Synthesis, Characterization and Biocidal Activities of Mixed-Ligand Complexes of Dioxomolybdenum(VI) Derived from Sulpha Drugs and 4-Benzoyl-3-methyl-l-phenyl-2-pyrazoline-5-one - Kumar, Ashish; Rai, Amit; Gupta, Mukesh (Asian Journal of Chemistry, 2011)
Dioxomolybdenum(VI) complexes with Schiff bases derived from 4-benzoyl-3-methyl-lphenyl- 2-pyrazoline-5-one and sulpha drugs sulphamoxole and sulphaguanol. The ligands and their MoO22+ complexes have been characterized on the basis of elemental analysis, electronic. I.R., 1H NMR spectral studies. On the basis of electronic spectral studies, octahedral geometry of all the complexes has been proposed. The in vitro antimicrobial activity of the investigated compounds was tested against the bacteria such as Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and fungi Candida albicans and Rhizopus stolonifer. The data indicate that all the metal complexes have higher antimicrobial activity than the free ligands.